ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA PT. JAVA MADANI PERKASA: ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA PT. JAVA MADANI PERKASA - Hadam, Hudha Ahsani; Sulistiyawan, Edy (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Rapid economic developments and quality human resources are a value in themselves for a company. Companies must be able to improve and make plans and evaluate each other's performance. This study aims to determine the factors that influence employee performance. The type of research is descriptive qualitative. The sampling technique uses the snowball sampling technique with a sample of 7 people. Data analysis is by data reduction, data presentation, drawing conclusions, and validation. The results of this study are that employee performance at PT. Java Madani Perkasa is not yet completely good. This is because there are several sub-indicators that have been running well, and there are several sub-indicators that have not been maximized. Work discipline factors and supervision from leaders make employee performance less than optimal. Compensation and leadership factors have been running optimally. This is known from the firmness of the leadership towards the performance and achievements obtained by employees.